Tatwiru Mawadi Ta’limi Kitabi LKS fi an-Nahwi Bikitabi Kayfa Haluk bi an-Nahwi? Litalamidi al Fasli al-‘Asyir fi al-Fasli ad-Dirosi al-Awal bi al-Madrosah Ast-Tsanawiyah Al-Islamiyah YATPI Godong - Nur Sahid; Hasan, Moh. Abdul Kholiq; Nashirudin, Muh. (Tarling : Journal of Language Education, 2023)
Abstract In fact, what happened at MA YATPI Godong was based on observations, many students still had difficulties in learning Arabic, especially in nahwu material, this is indicated by the number of students who took part in the Daily Assessment (PH) which was carried out at the end of one Basic Competence (KD) or some KD from each semester are still around 21-30% of students whose scores reach or above Minimum Completeness (KKM) while the rest still have difficulty answering the questions that have been provided, especially questions related to qoidah nahwu. This phenomenon is basically influenced by many factors, namely: 1) the learning process is not going well and not smoothly due to the lack of appropriate and adequate learning resources; 2) the teaching materials used are not relevant to the abilities and conditions of the students 3) the teaching materials do not meet content standards and curriculum standards; in the end the teacher is "confused" choosing the right book or teaching material according to the potential and learning needs of students; 4) Students get bored quickly due to less innovative teaching material designs where the use of language is difficult to understand and understand when students want to learn it. It is assumed that the development of nahwu teaching materials in Student Worksheets (LKS) through Research and Development (R&D) activities can improve learning effectiveness, motivate student interest in learning, as well as increase student competence. The development of this teaching material is limited to class X Arabic lessons in the first semester of Madrasah Aliyah which are then designed with attention to; a) material that is in accordance with Core Competency (KI) and Basic Competency (KD), b) material is reinforced with vocabulary notation (mufrodat), the application formula is based on qoidah nahwu especially when translating Indonesian text into Arabic, including the words interesting Arabic pearls related to lessons, c) various exercises (tadribat/drill).. Keywords: Reseach & Development, Development Of Teaching Materials, nahwu, LKS.